1966
DOI: 10.1113/jphysiol.1966.sp008023
|View full text |Cite
|
Sign up to set email alerts
|

The isolation of hyaluronic acid and chondroitin sulphate from kidneys and their reaction with urinary hyaluronidase

Abstract: SUMMARY1. Extracts of the cortex and the medulla of fresh kidneys from pigs, sheep and dogs were analysed for the presence of acid mucopolysaccharides.2. Acid mucopolysaccharides were found in the kidneys of the three species and were evenly distributed between cortex and medulla.3. The acid mucopolysaccharides isolated from either the medulla or the cortex of kidneys contained equal amounts of sulphated and nonsulphated fractions; these could be identified as chondroitin sulphate and hyaluronic acid, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1968
1968
1998
1998

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In connection with the distribution of these substances in the two anatomical zones the very few works based on chemical procedures reported in the literature are controversial. Dicker and Franklin [8] found that the concentrations of acid MPs were equal in the cortex and medulla in pigs, sheep and dogs. Castor, Greene and Prince [7] on the other hand reported a ratio of lU to Vo lor concentrations of acid MPs in the cortex and medulla in dog kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…In connection with the distribution of these substances in the two anatomical zones the very few works based on chemical procedures reported in the literature are controversial. Dicker and Franklin [8] found that the concentrations of acid MPs were equal in the cortex and medulla in pigs, sheep and dogs. Castor, Greene and Prince [7] on the other hand reported a ratio of lU to Vo lor concentrations of acid MPs in the cortex and medulla in dog kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…The production of monoclonal antibodies was essential for purification of sufficient enzyme for microsequencing. Hyaluronidase is present at high specific activity in human urine, approximately 100‐fold that of human plasma [7, 8]. It has been hypothesized that hyaluronidase plays a role in the action of antidiuretic hormone by increasing the permeability of the nephron walls, which have an ECM rich in HA [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Although several AGAG have been reported to be present in the kid neys, divergent data have been shown in differ ent species [1][2][3], Our recent studies indicated that the AGAG in human and bovine kidneys consisted of mainly heparan sulfates (HS) and dermatan sulfate (DS) with lesser components of hyaluronic acid (HA) and chondroitin 4-and 6-sulfates (C-4S. C-6S) [4,5].…”
mentioning
confidence: 99%